(untitled) (Global Journal of Human-Social Science, 2013)
The study aims at finding the application of Human Resources Information Systems (HRIS) in the private universities of Bangladesh. The paper is based on primary data collected through structured questionnaire from the HR personnel of 35 out of 61 Private Universities of Bangladesh. A five scale Likert technique has been used to investigate the interviewees’ opinion. The study reveals that only 22.9 % universities studied are using HRIS in full extent while 42.9% use HRIS to some extent. In 34.3% universities there is very limited applications of HRIS. Again, the highest use of HRIS is observed in recruiting and selection in private universities which is 80%. 74.3% universities use HRIS in their payroll system while the least use of HRIS is found in training and development of employees as only 14 (40%) universities apply HRIS technique for need assessment and train their employees. The paper explored that there is a gap between expected application of HRIS and present level of use in the selected private universalities. Among the main reasons of such gap Lack of infrastructure and high cost are found vital. The other reasons are lack of expertise in this field and insufficient training of the employees.